Taxonomic key to nymphs of the genus Amblyomma (Acari: Ixodidae) in Argentina, with description and redescription of the nymphal stage of four Amblyomma species - Martins, Thiago F. (2014)
In the present study, we provide morphological descriptions of the nymph of Amblyomma parvitarsum, A. tonelliae, and redescriptions of A. argentinae and A. sculptum. A taxonomic key, with relevant morphological characters illustrated by scanning electron micrographs, is provided for nymphs of the 24 species of the genus Amblyomma occurring in Argentina. Species included are A. argentinae, A. aureolatum, A. auricularium, A. boeroi, A. brasiliense, A. calcaratum, A. coelebs, A. dissimile, A. dubitatum, A. incisum, A. longirostre, A. neumanni, A. nodosum, A. ovale, A. parvitarsum, A. parvum, A. pseudoconcolor, A. pseudoparvum, A. rotundatum, A. sculptum, A. tigrinum, A. tonelliae, A. triste and A. varium. Principal morphological characters used for discrimination among species are presence/absence of auriculae, cornua and festoons with tubercles, size and shape of spurs of coxa I, margin and punctations of scutum, shape of basis capituli and length of cervical grooves. The geographical distribution of each tick species included in this work is presented and the importance of an accurate determination to species level of the Amblyomma nymphs to make epidemiological inferences is also discussed.